2016
DOI: 10.1590/2317-1782/20162015199
|View full text |Cite
|
Sign up to set email alerts
|

Fatores relacionados à disfagia orofaríngea no pós-operatório de cirurgia cardíaca: revisão sistemática

Abstract: RESUMO Objetivo Identificar os principais fatores relacionados à disfagia orofaríngea no pós-operatório de cirurgia cardíaca, por meio de uma revisão sistemática de literatura. Método Foi realizada pesquisa bibliográfica nas bases PubMed e ScienceDirect, utilizando os termos cardiac surgery, deglutition disorders e dysphagia. Critérios de seleção Foram selecionados artigos sem limitação de ano escritos em português, inglês ou espanhol e que referissem disfagia orofaríngea no pós-operatório de cirurgia cardí… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 33 publications
(44 reference statements)
0
3
0
2
Order By: Relevance
“…There are few studies that investigate the relationship between TI and changes in swallowing in pediatrics, there is a predominance of the publication of researches performed with adults in which a high prevalence of dysphagia is observed, with 44% to 85%, highlighting multifactor causes that include: oropharyngeal muscle inactivity, glottis lesions, mucosal inflammation and vocal fold ulcerations, as well as mechanical and sensory alterations (25)(26)(27) . A systematic review has shown that prolonged TI may be an independent predictor of dysphagia, and its use increases the risk of upper airway and larynx lesions, which in turn affect the mechanics, aerodynamics, and reflex protection of the upper airways (27) . The safe oral introduction is recommended as early as possible, since prolonged use of enteral probe interferes with the digestive and alimentary processes due to obstruction of the area, oral cavity desensitization, deprivation of oral stimuli.…”
Section: Figure 2 Distribution Of Classification Of Degree Of Pediatmentioning
confidence: 99%
“…There are few studies that investigate the relationship between TI and changes in swallowing in pediatrics, there is a predominance of the publication of researches performed with adults in which a high prevalence of dysphagia is observed, with 44% to 85%, highlighting multifactor causes that include: oropharyngeal muscle inactivity, glottis lesions, mucosal inflammation and vocal fold ulcerations, as well as mechanical and sensory alterations (25)(26)(27) . A systematic review has shown that prolonged TI may be an independent predictor of dysphagia, and its use increases the risk of upper airway and larynx lesions, which in turn affect the mechanics, aerodynamics, and reflex protection of the upper airways (27) . The safe oral introduction is recommended as early as possible, since prolonged use of enteral probe interferes with the digestive and alimentary processes due to obstruction of the area, oral cavity desensitization, deprivation of oral stimuli.…”
Section: Figure 2 Distribution Of Classification Of Degree Of Pediatmentioning
confidence: 99%
“…(OLIVEIRA et al, 2018) A ventilação mecânica (VM) prolongada pode ser um preditor independente de disfagia, e o uso do tubo orotraqueal aumenta o risco de lesões de vias aéreas superiores e laringe, que, por sua vez, afeta a mecânica, aerodinâmica e reflexo de proteção das vias aéreas superiores. (WERLE; STEIDL; MANCOPES, 2016) Na literatura, há estudos recentes com a população adulta e idosa sobre as definições de quais pacientes correm risco de disfagia. A IOT prolongada neste perfil de paciente (mais que 48 horas) é um fator definido como necessidade da avaliação precoce e mais detalhada da deglutição.…”
Section: Introductionunclassified
“…(OLIVEIRA et al, 2018) São poucos os estudos que investigam a relação entre IOT e alterações de deglutição em pediatria, há uma predominância da publicação de pesquisas realizadas com adultos na qual se observa alta prevalência de disfagia, com 44% a 85%, que destacam causas multifatoriais que incluem: inatividade do músculo orofaríngeo, lesões da glote, inflamação das mucosas e ulcerações de pregas vocais, além de alterações mecânicas e sensitivas. (WERLE;STEIDL;MANCOPES, 2016;SKORETZ et al,2014) Na população pediátrica se identificou a presença de disfagia em um número elevado da amostra de um estudo com associação estatisticamente significante entre o período de IOT maior de 24 horas em lactentes cardiopatas. (SOUZA et al, 2018) Não há protocolos validados disponíveis na literatura, podendo interferir nos resultados e desfechos.…”
Section: Introductionunclassified
“…Older people have decreased sensitivity, muscle force/strength, oral motor ability and salivary flow (1)(2)(3)(4)(5)(6)(7)(8) . These changes combined with dental problems, either acquired or degenerative disease, impair functions such as mastication, deglutition, and speech, and are risk factors for malnutrition, dehydration, health problems, disabilities, social isolation, and poor quality of life, resulting in additional health care costs (7,(9)(10)(11)(12)(13)(14) .…”
Section: Introductionmentioning
confidence: 99%